Historizing the City of Pekalongan - Allo, Katherina; Piliang, Yasraf Amir (ASPENSI in Bandung, Indonesia, 2015)
ABSTRACT: Historizing a collective life requires moments of time which construct a shared memory, moments in time that have brought a revolutionary change in the collective life, moments of marking that shared life in the progressive time sequencing, and moments of repetitions of what has been lived and experienced in that collectiveness. Without a moment of revolutionary change, the finding of that moment in history would seek into other forms of acknowledgement. Accordingly, the Pekalongan city in Central Java has a significant role in the development of batik production in Indonesia; and so, in 2011, this city was launched as the âworld batik cityâ by the government. This gesture was made to re-activate the dynamics of life in Pekalongan as it has experienced a decline in its industrial productivity. Other local potentials that support the characteristics of Pekalongan as a batik city have also been re-activated and upgraded, such as conserving the local batik kampongs, âKaumanâ and âPesindonâ, to be part of the national batik tourist destination areas. This writing will analyze how the life in Pekalongan underwent its historical process and how the external and internal factors interacted and weaved the various texture of life as it became the local color and identity of Pekalongan. Qualitative analysis methods are used in this writing to redefine what is commonly understood as a process of historization, and how this understanding can be used to look at the different contexts of life in Pekalongan. The finding of this research will show other possibilities that can be explored in the process of redefining and historizing the life of this city.KEY WORDS: Historizing, collective life, batik, Pekalongan, world batik city, tourist destination area, local color and identity, and redefining of history.Â Â About the Authors: Katherina Allo is a Doctoral Student at the Faculty of Fine Arts and Design ITB (Bandung Institute of Technology), Jalan Ganesha No.10 Tamansari, Bandung, West Java, Indonesia; and Prof. Dr. Yasraf Amir Piliang is a Lecturer at the Faculty of Fine Arts and Design ITB Bandung, West Java, Indonesia. For academic interests, corresponding author is: ar97ka@indo.net.idHow to cite this article? Allo, Katherina & Yasraf Amir Piliang. (2015). âHistorizing the City of Pekalonganâ in TAWARIKH: International Journal for Historical Studies, Vol.7(1) October, pp.99-110. Bandung, Indonesia: Minda Masagi Press, ISSN 2085-0980.Chronicle of the article: Accepted (August 29, 2015); Revised (September 27, 2015); and Published (October 28, 2015).